2011
DOI: 10.1111/j.1365-2958.2010.07524.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of Rho GTPases in Aspergillus niger uncovers conserved and diverged roles of Rho proteins within filamentous fungi

Abstract: SummaryRho GTPases are signalling molecules regulating morphology and multiple cellular functions including metabolism and vesicular trafficking. To understand the connection between polarized growth and secretion in the industrial model organism Aspergillus niger, we investigated the function of all Rho family members in this organism. We identified six Rho GTPases in its genome and used loss-of-function studies to dissect their functions. While RhoA is crucial for polarity establishment and viability, RhoB a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
159
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(168 citation statements)
references
References 75 publications
9
159
0
Order By: Relevance
“…According to their primary amino acid sequence and biochemical properties, the Ras superfamily is divided into different families: RAS (rat sarcoma), RHO (RAS homologs), RAB/ YPT (rat brain), ARF/SAR (ADP ribosylation factors), RAN (RAS-related nuclear) (649), ERA-like (Escherichia coli RASlike protein), SPG1/TEM1 (septum-promoting GTPase), and MIRO-like (mitochondrial Rho-GTPases) (650,651). In T. reesei, T. atroviride, and T. virens there are 105 genes encoding proteins of the RAS superfamily that are distributed in the different families mentioned above (36 genes in T. atroviride, 34 in T. reesei, and 35 in T. virens) ( Fig.…”
Section: Ras-gtpasesmentioning
confidence: 99%
See 3 more Smart Citations
“…According to their primary amino acid sequence and biochemical properties, the Ras superfamily is divided into different families: RAS (rat sarcoma), RHO (RAS homologs), RAB/ YPT (rat brain), ARF/SAR (ADP ribosylation factors), RAN (RAS-related nuclear) (649), ERA-like (Escherichia coli RASlike protein), SPG1/TEM1 (septum-promoting GTPase), and MIRO-like (mitochondrial Rho-GTPases) (650,651). In T. reesei, T. atroviride, and T. virens there are 105 genes encoding proteins of the RAS superfamily that are distributed in the different families mentioned above (36 genes in T. atroviride, 34 in T. reesei, and 35 in T. virens) ( Fig.…”
Section: Ras-gtpasesmentioning
confidence: 99%
“…In A. niger, six GTPases were identified that participate in diverse mechanisms, with sometimes overlapping functions (651). RhoA (homolog to RHO1; TR_119871, TA_298907, and TV_89761) is involved in the establishment of cell polarity and viability, while RacA (homolog to RAC1; TR_47055, TA_300919, and TV_81671) contributes to asexual development, septation, and branching mechanisms (651). Asexual reproduction in A. niger is also regulated by RhoB (homolog to RHO2; TR_21294, TA_156444, and TV_71661), RhoD (homolog to RHO4; TR_53562, TA_143775, and TV_31417), and CftA (homolog to CDC42; TR_50335, TA_298630, and TV_111456).…”
Section: Ras-gtpasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The n-hexane-soluble fraction was chromatographed over Si gel 60 (0.063 -0.200 mm) using vaccum liquid chromatography [14] with n-hexane and increasing amounts of ethyl acetate as eluents (250 mL each fraction). The second fraction (1730.0 mg) was washed with cold methanol, to afford pure KA (ent-kaur-16(17)-en-19-oic acid; 800.0 mg), which was identified by spectroscopic analysis and comparison with literature data [15].…”
Section: Isolation Of Kaurenoic Acid (Ka)mentioning
confidence: 99%